The mark of Cain : guilt and denial in the post-war lives of Nazi perpetrators - Kellenbach, Katharina von 1960- (Oxford University Press, 2013)
In "The Mark of Cain", Katharina von Kellenbach draws on letters exchanged between clergy and Nazi perpetrators, written notes of prison chaplains, memoirs, sermons, and prison publications to illuminate the moral and spiritual struggles of perpetrators after the war.